Lyon medical. - Societe Nationale de Medecine de Lyon.; Societe Nationale de Medecine et des Sciences Medicales (Lyons, Medipharly, 1869)
Issues for 1971- include a section with title: IML. Informations Medicales Lyonnaises.
Chemical abstracts
CIS abstracts
Excerpta medica
Index medicus
Life sciences collection
Vol. 191 omitted in numbering.
Keywords: Medicine -- Periodicals